The net impact of telework on restaurant revenues in Canada - Tahsin Mehdi; René Morissette (Economic and Social Reports, 2024)
The increase in work-from-home triggered by the COVID-19 pandemic has some implications for the Canadian economy such as its effects on revenues in the food services and drinking places. Using monthly provincial data from March 2020 to July 2022, this study quantifies the association between work-from-home and revenues in the food services and drinking places subsector.